Determinants Analysis of Public Perception of Waste Bank As An Alternative of Settlement Waste Management - Tri Hikmah Abdi Ningrum; Hilda Zulkifli; Rahmi Susanti (Research Centre of Inorganic Materials and Complexs, 2020)
The activities of the waste bank are giving a positive impact on the environment and increasing the public economy. This research aims to analyze the public perception of Kebumen Gemilang Sejahtera (KGS) waste bank in Kampung Iklim 2 Ilir, Palembang. The population of this study was 639 households and there were 90 households as respondents. This study used a quantitative method by cross-sectional design. The data collection instrument was a questionnaire, observations, interviews, and documentation. Data were analyzed by using multiple logistic regression. The results showed that the perception of the public (52.2%) of the waste bank categorized as good. Characteristics of the community are mostly aged ?42 years old (53.3%), mostly female (63%), highly educated (>SMA) of 87.8%, good knowledge (70.0%), including the length of stay at the old enough category (57.8%), and has the highest employment as a housewife (42.2%). The results of multiple logistic regression showed that the length of stay variable (OR=0.701) affects the public perception of the waste bank. Keywords: Waste, Waste Bank, Public Perception